Surgical treatment of metachronous metastases in different organs following radical nephrectomy - de Jesus, Carlos M.N. [UNESP]; Corrêa, Luiz Antonio [UNESP]; Trindade Filho, José C.S. [UNESP] (FapUNIFESP (SciELO), 2003)
Renal clear cell carcinoma (RCCC) is a neoplasia resistant to radio and chemotherapy, with surgical treatment being the procedure that is recognized for its curative treatment. This case report demonstrates the success of an aggressive surgical treatment for consecutive and late metachronous metastases following radical nephrectomy. Case report: Asymptomatic 50-year old man. During a routine examination, an incidental mass was found by renal ultrasonography. He underwent right radical nephrectomy due to RCCC in June 1992. During the follow-up metastases were evidenced in cerebellum on the seventh year, and in left lung and pancreas on the eighth year following the radical nephrectomy, with all of them successfully treated by surgical excision. Comments: The surgical excision of consecutive and late metachronous metastases in different organs arising from RCCC is feasible, being a good therapeutic alternative in selected cases.
Keywords: Cerebellum; Lung; Metastases; Pancreas; Renal cell carcinoma; Surgery; abdominal radiography; adult; brain metastasis; cancer grading; case report; cerebellum tumor; clear cell carcinoma; computer assisted tomography; craniotomy; excision; feasibility study; follow up; histopathology; human; human cell; human tissue; kidney carcinoma; kidney mass; lung metastasis; male; medical examination; nephrectomy; pancreas resection; pancreas tumor; quality of life; renography; splenectomy; surgical technique; symptomatology; thoracotomy; treatment outcome